Heterogeneous Integrated MEMS Enabled by AAO Process Technologies. (2nd November 2016) - Yildirim, Dogukan; Li, Guann-Pyng; Bachman, Mark
Abstract : An alternative approach to fabricate specialty MEMS devices by heterogeneous integration of dissimilar materials such as PCB substrates and neodymium magnets with anodic aluminum oxide (AAO) templates was demonstrated. The importance of the use of copper metal as an intermediate layer for wet chemical etching of AAO templates in order to release MEMS devices was presented. The assembling of dissimilar materials before the final wet chemical etch and release was introduced which is not possible with standard MEMS micromachining processes. The unique anisotropic etching feature, excellent dielectric with good mechanical properties, low cost, and compatibility with other materials and processes make AAO an attractive candidate material and process for manufacturing microdevices for many MEMS applications.